The governance of service delivery for the poor and women: A study of rural water supply in Ethiopia - Mogues, Tewodaj; Cohen, Marc J.; Birner, Regina; Lemma, Mamusha; Randriamamonjy, Josee; Tadesse, Fanaye; Paulos, Zelekawork (International Food Policy Research Institute, 2009)
This study presents empirical findings on drinking water supply in Ethiopia from a set of qualitative and quantitive surveys on rural public services. Access to safe drinking water is very low: 32% of the surveyed households use safe drinking water sources, and the average time to get to safe water sources during dry season ranged from 29 minutes to 82 minutes. The households covered in the Ethiopia survey may still have better access than the national average. Households identify drinking water as their main priority concern, yet they report high satisfaction rates and hardly take any action to complain. 71% of the households were very or somewhat satisfied with the quantity and 52% with the quality of drinking water, even though access was very low. What is surprising with these findings is the fact that a considerable share of the households identified water as their number one concern among a series of services in their area. This raises questions about how best to elicit information about satisfaction with rural services. Drinking water has undergone far-reaching decentralisation. The construction and major rehabilitation of drinking water facilities is managed by district water desks, which are backstopped by the Regional Water Bureaus. Water committees have been established, each of which usually manages one water facility. Making water committees inclusive seems challenging. Although bringing water to the household is predominantly a task undertaken by women (and their children), the study found that in all sites except for one, the water committee leaders were men The water committees also do not seem to be very effective in counteracting the top-down nature of service provision. The study found that in some cases the functioning of water facilities was compromised if the organization that constructed the facility did not take into account the community’s knowledge of water sources in determining where to locate the facility.